Efek Kesesuaian Kompensasi, Komitmen Organisasi, dan Kepuasan Kerja pada Kecenderungan Kecurangan - Angelina, Komang Reza; Utama, I Made Karya (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2024)
The study aims to analyze the effects of compensation suitability, organizational commitment, and job satisfaction on fraud tendencies. This study was conducted in LPDs throughout Buleleng Regency. This research uses Fraud Hexagon Theory as a grand theory. The number of respondents was 84 people consisting of chairman, secretary and treasurer in 28 LPDs who were selected using the area sampling method. Data collection used a closed questionnaire that was distributed directly. The analysis technique uses multiple linear regression analysis with the help of SPSS 26. The research results show that compensation suitability, organizational commitment and job satisfaction have a negative and significant effect on the tendency to fraud, both partially and simultaneously. This result means that the higher the suitability of compensation, organizational commitment and job satisfaction, the tendency for fraud to decrease.